A vivência da fissura por crack: rebaixamento de valores e estratégias utilizadas para o controle - Chaves, Tharcila Viana [UNIFESP] (2009)
Objective: To understand, through the discourse of individuals who have already consumed crack: how their cravings proceed; what behavioral patterns are developed with such cravings and what strategies users follow to hold back their cravings. Methodology: This was a qualitative study using an intentional sample with selection criteria, composed of crack users (n=31) and former users (n=9) of both sexes, aged 18 to 50 years. The subjects belonged to 12 different chains and were recruited using the snowballing technique. In-depth semi-structured interviews were held with recruits until the theoretical data saturation point of the sample was reached. The interviews were transcribed literally and the scripts then underwent content analysis in order to elaborate grounded inferences and hypotheses from the discourse. Results and Discussion: The interviewees were equally distributed regarding gender. They ranged over all educational levels and most of them had little money. In addition to the known cravings felt through abstaining from crack and through environmental and emotional paths, a third type of craving was observed, induced by the effect of the crack itself. As soon as the users took the first drag, they developed a compulsion to consume it, leading them to uninterrupted use until the supply ran out or they reached exhaustion. This type of craving appeared to be a strong factor in maintaining episodes of bingeing. Such episodes were the greatest factors responsible for lowering users’ values, thereby impelling them to act unconventionally to obtain the drug, with highly aggressive events. The interviewees not only had strategies for relieving their cravings, but also had tactics to avoid their development, both of pharmacological and of behavioral nature. Conclusions: The craving by crack, among other symptoms, triggers compulsion, risk behavior, suffering, aggression and binge pattern of consumption, which may be related to the development of dependence. Bingeing on crack may be caused by the craving that the effect of the crack itself induces. Users’ own measures for dealing with their cravings for crack may constitute an important tool for improving their treatment.